2012
DOI: 10.1063/1.4738191
|View full text |Cite
|
Sign up to set email alerts
|

Chaos in neurons and its application: Perspective of chaos engineering

Abstract: We review our recent work on chaos in neurons and its application to neural networks from perspective of chaos engineering. Especially, we analyze a dataset of a squid giant axon by newly combining our previous work of identifying Devaney's chaos with surrogate data analysis, and show that an axon can behave chaotically. Based on this knowledge, we use a chaotic neuron model to investigate possible information processing in the brain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 53 publications
0
21
0
Order By: Relevance
“…Important examples of such fast-slow dynamics [6][7][8] are found in chemical reactions, laser dynamics and in mathematical neuron models. Understanding how to generate and control a burst of spikes in neuron cells, and how chaotic behavior can appear in such systems [9][10][11] are some of the most fundamental questions in neuroscience. The key questions that we want to address are: how is this chaotic behavior organized?…”
mentioning
confidence: 99%
“…Important examples of such fast-slow dynamics [6][7][8] are found in chemical reactions, laser dynamics and in mathematical neuron models. Understanding how to generate and control a burst of spikes in neuron cells, and how chaotic behavior can appear in such systems [9][10][11] are some of the most fundamental questions in neuroscience. The key questions that we want to address are: how is this chaotic behavior organized?…”
mentioning
confidence: 99%
“…15 in the RWC Music Database (Musical Instrument Sound). Previous studies on squid giant axons have demonstrated the chaotic nature of the underlying dynamics20212223. These time-series are both scalar and real-valued.…”
Section: Resultsmentioning
confidence: 99%
“…Hirata et al 38 revisit a data set collected from the giant axon of the squid (the preparation used in Hodgkin and Huxley's Nobel Prize winning work in which the dynamics of action potentials were first modeled). The authors show that a relaxed, numerically adapted version of Devaney's criteria for chaos 39 identifies the neuron's voltage time series as chaotic, and also briefly describe a simple mapping that produces deterministic chaos in a neural network model of memory recall.…”
Section: The Papers In This Issuementioning
confidence: 99%
“…While most of these papers were prepared independently (one pair 30,31 does share three authors and another 38,40 shares one), they nicely illustrate common interests in nonlinear dy-namics. In particular, computational methods (rigorously based, as in Refs.…”
Section: The Papers In This Issuementioning
confidence: 99%
See 1 more Smart Citation